Alpha Generation and Digital Literacy for the Future of the Nation - A.Nur Aisyah Rusnali (State Islamic Institute of Bone, Indonesia, 2021)
Digital skills are a basic need that must be owned by everyone in today's digital world. Digital skills are the ability to operate digital devices and to be able to use them intelligently and wisely. To grow digital skills, a digital literacy movement is needed. The alpha generation is the generation born between 2010 and 2025. Because we live in the digital era, the Alpha generation needs digital skills. This of course can be obtained from the digital literacy movement. This research was conducted to examine more deeply the role of digital literacy in growing digital skills for the Alpha generation as the nation's next generation. The research method used is Library Research, namely by collecting literature related to the theme to be studied.